HvGCN2 silencing in barley displays enhanced Blumeria graminis f. sp. hordei susceptibility - Öztürk, İbrahim Kutay and Ersoy, Figen and Akkaya, Mahinur Sezener (Archives of Biological Sciences, 2018)
Paper description: Arabidopsis thaliana GCN2 (AtGCN2) was shown to be involved in disease resistance against biotrophic and necrotrophic pathogens, suggesting a similar role for Hordeum vulgare GCN2 (HvGCN2). This is the first study showing the potential importance of HvGCN2 in powdery mildew disease of barley. Under susceptible condition, powdery mildew development was increased in HvGCN2 silenced plants compared to control plants, supported both by hyphal length and number of germinated spores. However, no difference was observed between HvGCN2-silenced and control plants under resistant condition. Abstract: Powdery mildew disease, caused by Blumeria graminis f. sp. hordei (Bgh), which belongs to the order Erysiphales, is a major crop disease. The general control nondepressible-2 (GCN2) gene of barley was previously found to be overexpressed during the powdery mildew resistance response. Recently, Arabidopsis thaliana GCN2 (AtGCN2) was shown to be involved in disease resistance against biotrophic and necrotrophic pathogens. In order to understand the function of Hordeum vulgare GCN2 (HvGCN2) in the barley powdery mildew resistance response, this gene was silenced by barley stripe mosaic virus (BSMV), mediated by virus-induced gene silencing (VIGS). This is the first study showing the potential importance of HvGCN2 in powdery mildew disease of barley. Based on our observations, when HvGCN2 was silenced on average by 53.5%, Bgh development was increased by 18.7 to 32.1%, which was determined by primary, secondary and longest hyphae measurements. The number of germinated spores also increased 2.8-fold in HvGCN2 silenced plants compared to control plants (BSMV:00). On the other hand, under the resistant condition, no difference was observed in HvGCN2-silenced plants compared to non-silenced lines although the gene was found to be overexpressed in incompatible interaction. https://doi.org/10.2298/ABS171017012O Received: October 17, 2017; Revised: February 20, 2018; Accepted: March 20, 2018; Published onlione: March 29, 2018 How to cite this article: Ozturk IK, Ersoy F, Akkaya MS. HvGCN2 silencing in barley displays enhanced Blumeria graminis f. sp. hordei susceptibility. Arch Biol Sci. 2018;70(3):…